How Trump and the Christian right saved LGBTI human rights: a religious freedom mystery - Burack, Cynthia (SUNY Series in Queer Politics and Cultures, 2022)
Traces the Trump administration's surprising support for LGBTI human rights abroad to Trump's indifference and the cynicism and political interests of Christian conservative elites.